TAX BEHAVIOR: AVOIDANCE VS EVASION (ANALYSIS OF INDICATORS OF THE EUROPEAN UNION AND THE WORLD) - Tamara Merkulova (Соціальна економіка)
The article is devoted to the study of behavioural aspects of taxation. A significant problem of effective taxation is taxpayers’ reduction of tax liabilities through shortcomings in tax laws, uncertainty in their statements, direct violation of tax norms, and the use of illegal schemes to reduce the tax base. Taxpayer behaviour is of key importance for the effectiveness of tax policy, filling the budget, and performing state functions, which determines the relevance of this issue.